(untitled) (Eurasian Journal of Ecology, 2020)
The article presents the results of studies of the state of the sewage sump, which allow to determine the degree of contamination, and choose the most environmentally and economically expedient method of cleaning them for use in the irrigation system of plantings. Currently, the problem of finding alternative sources of water supply, solving the problem of water shortage even for irrigation of plantings, not to mention the needs of irrigated agriculture, is of paramount importance for the city of oil workers of Zhanaozen. Relevant and timely is the geochemical assessment of water pollution and bottom sediments of the sewage settling tank of urban sewage treatment plants, which allows us to analyze the special situation in the area of the settling tank and develop ways to solve the use of these waters for surface irrigation of urban plantations. Water sampling was carried out in accordance with GOST R 51592-2000. Selection and storage of bottom sediments were carried out in accordance with the requirements of GOST 17.1.5.01-80. Water pH was determined using a portable Hanna pH meter. Determination of oil content was carried out according to a certified method of extraction-photometric method by the analyzer, the content of petroleum products “AH-2”. Statistical data processing was performed in the environment of the analytical software interface Statistica 10. The choice of the analysis method using Kruskal-Wallis ANOVA test statistics was determined by a small volume of research samples with different distribution laws. GIS family programs (Google Maps, SAS Planet) were used to create a schematic map of the area where the wastewater sump is located. The results of the assessment of the degree of contamination of the sump, located almost within the city of Zhanaozen, with an insufficient degree of water treatment, which turns it into a “man-made” object, allow us to develop and choose the most economically feasible and environmentally friendly solar water treatment plant, in order to solve the problem of irrigation water shortage, for the green spaces of the city of oil workers. Key words: Sedimentation tank, waste water, bottom sediments, heavy metals, water pollution index, total pollution index.